Novel Glibenclamide–Phospholipid Complex for Diabetic Treatment: Formulation, Physicochemical Characterization, and in-vivo Evaluation - Rathor, Sandeep; Bhatt, DC (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Formulation of phospholipid complex is an ideal approach to improve the solubility of poorly soluble drugs. Objectives: This study has been aimed to prepare a novel glibenclamide-phospholipid complex by using the solvent evaporation technique. Materials and Methods: Because glibenclamide is a weakly soluble medication, complexing it with phospholipids is an excellent way to enhance its solubility. The phospholipid complex of Glibenclamide was produced using the solvent-evaporation technique to enhance its oral efficacy. The formulation was characterized and evaluated by various parameters including FTIR, DSC, PXRD, SEM, TEM, in vitro drug release, and in vivo pharmacokinetic studies in Wistar rats plasma. According to studies, the Glibenclamide phosphates combination is significantly more water-soluble than the physical combination and pure Glibenclamide. The oral bioavailability of the glibenclamide-phospholipids complex was measured by using HPLC in Wistar rats’ plasma. Results: There was no substantial interaction between the medication and the phospholipid in the formulation, according to the FTIR and PXRD findings. The morphology of the formulation was verified by SEM and TEM investigations, indicating that the crystalline form had been converted to an amorphous form. The glibenclamide-phospholipids complex had a greater peak plasma concentration (5.1 vs. 3.8 g/mL), its AUC was higher (14.65 vs. 11.81 μgh/L), and its T1/2 was longer (2.4 vs. 3.1 hr), showing that it enhanced drug dissolution rate. Conclusion: The findings showed that increasing the oral bioavailability of waterinsoluble medicines by phospholipid-complexation is a potential approach. The results showed that phospholipid-complexation may be used to enhance the oral bioavailability of water-insoluble drugs.
Keywords: Glibenclamide; Glibenclamide–phospholipid complex; Pharmacokinetic; Oral; bioavailability